Pengembangan Media Pembelajaran Booklet untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas IV di SDN 7 Sungai Raya - Ningsih, Ayu; Afryaningsih, Yunika; Listiarini, Yuni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research and development aims to produce booklet learning media that is feasible, practical and effective. The problem in the learning to read process is the lack of reading comprehension skills in class IV due to the lack of learning media during the learning to read process, making students tend to get bored with learning and not interested in participating in learning to read. So many students can read but don't understand what they read. This is what encourages researchers to try to develop booklet learning media. The type of research used in this research is the Research and Development (R&D) method or research and development developed using the ADDIE model which consists of five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The data analysis used is quantitative and qualitative analysis. The results of this research and development are based on research results from experts, the results obtained from media experts were 95%, material experts were 100%, and language experts were 93.75% to obtain feasibility. Practicality results were obtained from student response questionnaires and effectiveness results were obtained from observational assessments of reading comprehension skills